Decomposition analysis method in linear and nonlinear differential equations - Haldar, Kansari (CRC Press is an imprint of Taylor & Francis Group, an Informa Business, 2016)
Decomposition Analysis Method in Linear and Non-Linear Differential Equations explains how the Adomian decomposition method can solve differential equations for the series solutions of fundamental problems in physics, astrophysics, chemistry, biology, medicine, and other scientific areas. This method is advantageous as it simplifies a real problem to reduce it to a mathematically tractable form